«POYTAXT» SO‘ZINING LUG‘AVIY MА’NOSI VA TARIXIY-GEOGRAFIK, LINGVISTIK TALQINI - Bayqabilov, Х.M. (SCIENCE and SOCIETY, 2023)
The article describes the dictionary meaning and the historical-geographical, linguistic interpretation of the word "capital". The article provides information on the linguistic analysis of the word "city" in different foreign languages and synonyms for the word "capital".
Keywords: capital; special federal district; city; urban settlements; administrative center; city-state; palace; orda